Venture failure, stigma, and impression management: A self‐verification, self‐determination view - Shepherd, Dean A.; Haynie, J. Michael (Strategic Entrepreneurship Journal, 2011)
We offer a theoretical basis for understanding how and to what end entrepreneurs employ impression management strategies in response to the negative attributions associated with the stigma of venture failure. Our framework offers counterintuitive insights into why some entrepreneurs stigmatized by failure will use impression management strategies to align their conception of self with how others perceive them—even if that means adopting a negative view of self. Our model highlights a potential paradox related to competing individual (the entrepreneur) and organizational goals, with regard to actions positioned to enhance the psychological well‐being of the failed entrepreneur. Copyright © 2011 Strategic Management Society.